Efektivitas Model Pembelajaran Somatic, Auditory, Visual, Intellectual (SAVI) terhadap Pemahaman Siswa pada Mata Pelajaran Fiqih di MTs Negeri 2 Cilacap - Malda Shofiyatunnisa; Irma Dwi Tantri (Jurnal Budi Pekerti Agama Islam, 2026)
The purpose of this study was to explore the extent to which the Somatic, Auditory, Visual, and Intellectual (SAVI) learning model can improve students' understanding of Fiqh at MTs Negeri 2 Cilacap. The background of this study is the low level of student understanding, which is caused by a teaching approach that is still teacher-focused, resulting in less student involvement in the learning process. This study used a quantitative approach with a Quasi-Experimental Non-Equivalent Control Group Design. The research sample consisted of two classes, namely the experimental class and the control class, each containing 31 students. The research instrument was a Fiqh understanding test whose validity and reliability had been tested. The resulting data analysis test, which was carried out using a normality test, showed that all test items were declared valid (0.101 > 0.05), as well as the homogeneity test (0.773 > 0.05) and the t-test (0.025). so that Ho was rejected and Ha was accepted, meaning there was a difference between the control class and the experimental class. The results of the study show the effectiveness of the SAVI learning model on students' understanding of Islamic jurisprudence at MTs Negeri 2 Cilacap.